At the evaluation of fluctuation asymmetry of green plantings of Karaganda region’s industrial cities - Ishmuratova, M.Yu.; Konkabaeva, А.Е.; Tleukenova, S.U.; Matveev, A.N.; Pudov, A.M.; Kanafina, B.A.; Temirov, A.S. (Fundamental and Experimental Biology, 2015)
Studying of specific structure and condition of green plantings at the territory of industrial centers of the Karaganda region (Karaganda, Temirtau, Balkhash, Zhezkazgan) is carried out. The specific structure of wood flora on the surveyed points is presented by 13–18 main species. Vitality of wood plants made from 1 to 3 points. On a scale of the characteristic of environment by means of the fluctuating asymmetry, wood plants have got five marks on all research sites, which ecosystems were in areas with extraordinary anthropogenic pressure.